Returns from Motorised Traditional Craft in Veraval Coast - R.S., Manohar Doss; V., Annamalai; Putra, Pravin; M.K., Kandoran (Fishery Technology, 2025)
Economic performance of motorised traditional craft operating in Gujarat Coast has been worked out. Average investment on a fishing unit with 12 m craft, 8 HP engine and a complement of gear, works out to Rs. 1.11 lakhs. Average annual maintenance cost works out to 21% of the investment cost. Highest percentage share of maintenance go for engine repair, annual rate of return on investment is 8.72%. Internal Rate of Return of investment works out to 28%. Sensitivity analysis has been carried out on IRR.